Технологические приемы улучшения теплового режима выращивания кристаллов GaAs методом Чохральского - Kovtun, G. P.; Kravchenko, A. I.; Kondrik, A. I.; Shcherban', A. P.; Kondrik, A. I. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
For the Czochralski method with liquid encapsulation of the melt and an additional heater immersed in the flux, the dependence of the temperature gradient G near the crystallization front in GaAs crystals on the heater power, its distance from the crystal, as well as on the conditions of thermal shielding of the crystal and flux at different ratios of heat flows through the bottom and wall of the crucible has been studied. The conditions under which the best results are achieved (taking into account the values of G and the uniformity of their radial distribution) are demonstrated.